A model for the non-thermal emission of the very massive colliding-wind binary HD 93129A - del Palacio, Santiago (2016)
Recently, the wind collision region of the system HD 93129A was resolved for the first time using very large baseline interferometry. This system is one of the most massive known binaries in our Galaxy. In this work we develop a broadband radiative model for the wind collision region. The model takes into account the evolution of accelerated particles streaming along the shocked region, their emission through different radiative processes, and the attenuation of the radiation while it propagates across all local fields. We reproduce the available radio data, and analyze the consequent detectability of the source in hard X/gamma-rays. We predict how the emission from the system will evolve in the forthcoming years when the stars come closer, and we also provide synthetic radio maps that allow to interpret the future observations with very large baseline interferometry in 2.3 GHz and 8.6 GHz. According to our results, the non-thermal emission from this system will enhance in the near future. With instruments such as NuSTAR, Fermi, and CTA, it will be possible to determine whether the relativistic particle content is hadron or lepton dominated, and other parameters such as the strength of the magnetic field in the wind collision region and, indirectly, the magnetic field in the surface of the very massive stars.